PERBANDINGAN PERSEPSI PADA MATERIAL-MATERIAL UPCYCLE DO IT YOUR SELF (DIY) DENGAN PENDEKATAN MATERIAL DRIVEN DESIGN - Devanny Gumulya (Jurnal Dimensi Seni Rupa dan Desain, 2019)
AbstractIn the past five years, technology advances and fabrication feasibility like 3d printing has boost the do it your self movement, and it is expanding beyond products to the materials that is labeled as diy-materials. DIY-materials are created through individual or collective through self-production practices that involves a lot of creativity and innovative approach. One of these diy-materials is upcycle material. The pollution on landfill and ocean has encouraged us to be more responsible for the wastewe create by recycling the waste and make it as new material. Egg shells and LPDE plastic bag waste are discussed in this paper. The perception between the two diymaterials upcycle is compared using material driven design approach (MDD). In MDD, sensorial, interpretation, afective and perfomative dimensions shape people's perception and experience toward the materials. This approach is needed, to give waste material a new life and for it to be accepted on the market. Results from studies are thedo and don'ts for product design process using egg shells and ldpe plastic bag waste. Imperfections through pattern, texture and color are the qualities that people seek when interacting with diy-upcycle materials. These qualities can't be found in mass produced industrial made material. Design principle such as balance, contrast, emphasis, movement, pattern, rhythm, and unity/variety are need to be well planned in making pattern, texture and color, because if it is done wrong, the material will beperceived back as waste.  AbstrakDalam lima tahun terakhir kemajuan teknologi informasi dan kemudahanfabrikasi seperti 3d printing mendorong tren do it your self berkembang pesat mulai dari pembuatan produk hingga ke material. Material diy adalah material yang dibuat oleh individu ataupun kolektif melalui prosespengolahan yang inventif. Salah satu material diy yang banyak diulik adalah material daur ulang yang banyak dikenal dengan material upcycle. Tuntutan pencemaran lingkungan di darat dan air mendorong manusia untuk bertanggung jawab dengan sampah yang dihasilkan dengan mencoba mendaur ulang limbah dan menjadikannya material yang dapat dipakai ulang. Dalam paper ini dua material yang dibahas adalah material daur ulang dari limbah cangkang telur dan limbah kantong plastik LDPE. Kedua material ini dibandingkan persepsinya dengan pendekatan material driven design (MDD). Dalam MDD, dimensi sensorial, interpretatif, afektif dan performatif  material membentuk persepsi dan pengalaman orang akan sebuah material. Pendekatan ini dibutuhkan agar material limbah ini dapat keluar persepsinya sebagai limbah yang kotor dan terbuang menjadi material baru yang dapat diterima di pasar. Hasil dari kajian ini adalah rekomendasi bagi perancangan desain produk dengan material limbah cangkang telur dan limbah kantong plastik LDPE. Hal-hal yang perlu ditekankan dari material diy adalah ketidaksempurnaan yang ditandakan melalui pola, tekstur dan warna, karena hal ini tidak ditemui pada material buatan industri massal. Prinsip-prinsipdesain seperti balance, contrast, emphasis, movement, pattern, rhythm, and unity/variety harus direncanakan dengan baik dalam pembuatan pola, tekstur dan warna, karena bila salah material diy dapat dipersepsikan negatif.